Poznavanje funkcij mišic medeničnega dna in pomena komplementarnih konservativnih pristopov za njihovo krepitev pri ženskah - Dovgan, Patricija (Obzornik zdravstvene nege, 2018)
Introduction: Urinary incontinence is often the result of weakened pelvic floor muscles. The purpose of the study was to establish how much women knew about the pelvic floor muscle functions and how useful they found the complementary conservative approaches for pelvic floor muscles strengthening. Methods: The exploratory quantitative research method was used. The questionnaire was prepared on the basis of the literature review and was designed with the 1KA online tool. The sample was composed of women aged between 20 and 64 (n = 356). Descriptive statistics and data factor analysis were performed. Results: 190 of the respondents (52.4 %) did not perform any exercises to strengthen pelvic floor muscles. The results showed that 12 respondents (7 %) use devices for effective strengthening of pelvic floor muscles. Discussion and conclusion: Factor analysis was used to confirm the usefulness of the instrument used. The surveyed women know the functions of the pelvic floor muscles associated with urinary incontinence well, but they do not do much to strengthen the pelvic floor muscles. They only perceive sexual devices as devices used for fun, but are not aware of the possibility of using them to strengthen the pelvic floor muscles.
Keywords: health education; nursing care; physical activity; sexual devices; spolni pripomočki; telesna aktivnost; urinary incontinence; urinska inkontinenca; zdravstvena nega; zdravstvena vzgoja